Knockdown of lncRNA NEAT1 suppresses multiple myeloma progression via the miR-133a-3p/ARPC5 axis - Li, Xin; Zhang, Peng; Meng, Zhenzhen; Luo, Shanshan (Journal of Radiation Research and Applied Sciences, 2025)
Long non-coding RNA nuclear paraspeckle assembly transcript 1 (LncRNA NEAT1) has been implicated in multiple myeloma (MM) pathogenesis, with elevated expression correlating with disease progression and poor clinical outcomes. This study systematically investigated the molecular pathways through which NEAT1 contributes to MM pathogenesis. We first characterized NEAT1 expression patterns in MM patients and MM cell lines. Functional studies were performed in NCIH929 and U266 cell lines through gain-of-function (overexpression plasmids) and loss-of-function (small interfering RNA -mediated knockdown) approaches, with assessment of proliferation, invasion and apoptosis. Mechanistic studies employed dual-luciferase reporter assays to validate direct interactions between NEAT1/miR-133a-3p and miR-133a-3p/ARPC5. Rescue experiments elucidated functional relationships within this regulatory axis. Therapeutic potential was evaluated in xenograft models using NEAT1-depleted NCIH929 cells. Expression analysis revealed that NEAT1 was upregulated 2.2-fold in MM patients (P < 0.01), while miR-133a-3p was downregulated 3.1-fold (P < 0.01) and ARPC5 mRNA levels was increased 2.0-fold (P < 0.01). NEAT1 overexpression notably enhanced MM cell proliferation and invasion, and suppressed apoptosis (P < 0.01). Conversely, NEAT1 knockdown yielded opposite effects (all P < 0.01). Mechanistically, miR-133a-3p was a target gene of NEAT1 and negatively regulated by NEAT1. The inhibition of miR-133a-3p counteracted the tumor-suppressive effect of NEAT1 knockdown on MM cell progression. Furthermore, ARPC5 was validated as a downstream target of miR-133a-3p, and the overexpression of ARPC5 nullified the inhibitory effect of miR-133a-3p overexpression on MM cell progression (P < 0.01). Additionally, NEAT1 knockdown inhibited ARPC5 expression in MM cells (P < 0.01). ARPC5 overexpression abrogated the inhibitory effects of NEAT1 knockdown on MM cell progression (P < 0.01). Additionally, NEAT1 depletion significantly suppressed tumor growth in vivo (P < 0.01). LncRNA NEAT1 knockdown suppressed proliferation and invasion, and facilitated apoptosis of MM cells via targeting the miR-133a-3p/ARPC5 pathway. This study is the first to demonstrate that NEAT1 promotes MM progression by sponging miR-133a-3p to upregulate ARPC5, revealing a novel therapeutic axis. [Display omitted]